2017
DOI: 10.1021/acs.nanolett.6b04663
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Transport at a Rectifying GaAs Contact

Abstract: In most single- or few-molecule devices, the contact electrodes are simple ohmic resistors. Here we describe a new type of single-molecule device in which metal and semiconductor contact electrodes impart a function, namely, current rectification, which is then modified by a molecule bridging the gap. We study junctions with the structure Au STM tip/X/n-GaAs substrate, where "X" is either a simple alkanedithiol or a conjugated unit bearing thiol/methylthiol contacts, and we detect current jumps corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…The prepared metal-molecule(s)-semiconductor devices behave like Schottky diodes as discussed in the Introduction, and we reported on the effect of the molecular wire (the insulator of the Schottky diode) in our previous publication. 1 We found that on heavily doped nGaAs HD the rectication ratio RR, which is dened as the ratio of the current owing in forward bias to the current owing in reverse bias at a xed magnitude of bias potential, was remarkably dependent on the nature of the molecular wire employed. The saturated a,u-alkanedithiols (ADT) 4ADT, 5ADT, 6ADT and 7ADT showed an almost constant RR at AE1 V of approximately 12 ( Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The prepared metal-molecule(s)-semiconductor devices behave like Schottky diodes as discussed in the Introduction, and we reported on the effect of the molecular wire (the insulator of the Schottky diode) in our previous publication. 1 We found that on heavily doped nGaAs HD the rectication ratio RR, which is dened as the ratio of the current owing in forward bias to the current owing in reverse bias at a xed magnitude of bias potential, was remarkably dependent on the nature of the molecular wire employed. The saturated a,u-alkanedithiols (ADT) 4ADT, 5ADT, 6ADT and 7ADT showed an almost constant RR at AE1 V of approximately 12 ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The charge carrier depletion at the semiconductor interface results in a larger charge ow when the junction is biased in one direction (forward bias) than the other (reverse bias), resulting in asymmetric I-V characteristics. We recently reported this behaviour using gallium arsenide (GaAs) as electrode, 1 and it was also demonstrated on silicon, 7 in both cases using a molecular wire with appropriate contacting ends and a Au metallic electrode. Using a semiconducting electrode allows for a ner tuning of the junction properties, as the type of its doping (n-or p-type), can be used to control the nature of the majority charge carrier, and the doping density will affect the concentration of charge carriers (and therefore the semiconductor conductivity), and the size of the space charge layer.…”
Section: Introductionmentioning
confidence: 92%
“…Another new concept for a metal‐molecule‐semiconductor device employing Au tip/molecule/GaAs substrate was achieved by Nichols et al With low doped GaAs, molecular junctions displayed rectification ratios as particularly high as >10 3 in the dark and a high photocurrent in reverse biases. It should be noticed that the replacement of gold electrodes with conventional GaAs or silicon semiconductor materials reduces the gap between molecular electronic and traditional microelectronics . Figure B shows a porphyrin‐C60 dyad molecule in the gold‐ITO (indium tin oxide) tunnel junction.…”
Section: Stimuli‐responsive Materials For Electrical Switchesmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] In particular, scanning tunneling microscopy shows strong ability to form different types of molecular junctions (tip and substrate can be different materials), which makes it possible to realize new type of functional devices and to observe novel phenomenon. [18][19][20][21] Meanwhile, the effects of molecular anchors, [22][23][24][25] electrode material, [7,8] and external environment on the properties of single-molecule junctions have been investigated, [25][26][27][28] which is a large step toward the construction of functional molecular electronic devices. Nonetheless, a number of challenges still need to be overcome before single-molecule devices can be widely used as commercial products.…”
Section: Doi: 101002/smll201703815mentioning
confidence: 99%